Acute hepatitis attack after exposure to telithromycin - DENİZBAŞI ALTINOK, ARZU; ÇELİKEL, ÇİĞDEM (ELSEVIER, 2007)
Introduction: Anti biotic-associated hepatotoxicity is rare. With widespread use of antimicrobial agents, however, hepatic injury occurs frequently, and among adverse drug reactions, idiosyncratic reactions are the most serious. Case summary: A 25-year-old male patient, with a height of 175 cm and weight of 72 kg presented to Marmara University Hospital Emergency Department, Istanbul, Turkey, with 5 days' history of jaundice, malaise, nausea, and vomiting. He had been prescribed telithromycin 400 mg/d PO to treat an upper respiratory tract infection 7 days prior. Admission laboratory tests were as follows: alanine aminotransferase, 67 U/L (reference range, 10-37 U/L); aspartate aminotransferase, 98 U/L (10-40 U/L; alkaline phosphatase, 513 U/L (0-270 U/L; gamma-glutamyltransferase, 32 U/L (7-49 U/L); amylase, 46 U/L (0-220 U/L); total bilirubin, 20.1 mg/dL (0.2-1.0 mg/dL); direct bilirubin, 14.8 mg/dL (0-0.3 mg/dL); and albumin, 4.7 mg/dL (3.5-5.4 mg/dL). No toxin, alcohol, or other drugs were reported. The patient had suffered a previous episode of acute hepatitis of unknown origin, that occurred after telithromycin usage. Both incidents occurred within a year. Discussion: Telithromycin is the first of the ketolide antibacterials to receive US Food and Drug Administration approval for clinical use. It has been associated with infrequent and usually reversible severe hepatic dysfunction. Based on a score of 8 on the Naranjo adverse drug reaction probability scale, telithromycin was the probable cause of acute hepatitis in this patient, and pathological findings suggested drug-induced toxic hepatitis. Recurrence of hepatitis attack might have been avoided if the initial incident had been communicated to the attending physician who prescribed telithromycin the second time. Conclusion: Here we report a case of acute hepatitis probably associated with the administration of telithromycin. (Clin Ther. 2007;29:1725-1729) Copyright (c) 2007 Excerpta Medica, Inc.
Keywords: telithromycin; hepatitis; case report; antibiotic; jaundice; hepatotoxicity; RECURRENT; ANTIBIOTICS